2006
DOI: 10.1211/jpp.58.7.0008
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative effect of salvianolic acid A on rat hepatic stellate cells

Abstract: Suppression of activation or proliferation, or induction of apoptosis in hepatic stellate cells (HSCs) have been proposed as therapeutic strategies against liver fibrosis. Salvia miltiorrhiza has been reported to exert antifibrotic effects in rats with hepatic fibrosis, but its mechanisms of action remain to be clarified. We have investigated the effects of salvianolic acid A (Sal A), an active principle from S. miltiorrhiza, on the proliferation-related biomarkers in a cell line of rat HSCs (HSC-T6) stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…3). So far, 13 of the components found within MLC601 have been found to have the ability to reverse and prevent events associated with Aβ-induced toxicity [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45]. Specifically, radix salviae miltiorrhizae, radix paeoniae rubrae, radix angelicae sinensis, radix astragali, rhizoma chuanxiong and Carthamus tinctorius have all been shown to ameliorate critical toxic events within the amyloid cascade hypothesis (fig.…”
Section: Introductionmentioning
confidence: 99%
“…3). So far, 13 of the components found within MLC601 have been found to have the ability to reverse and prevent events associated with Aβ-induced toxicity [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45]. Specifically, radix salviae miltiorrhizae, radix paeoniae rubrae, radix angelicae sinensis, radix astragali, rhizoma chuanxiong and Carthamus tinctorius have all been shown to ameliorate critical toxic events within the amyloid cascade hypothesis (fig.…”
Section: Introductionmentioning
confidence: 99%
“…Following liver injury of any etiology, HSCs undergo a response known as ''activation,'' which is the transition of quiescent cells into proliferative, fibrogenic, and contractile myofibroblasts [2]. Several studies recently reported that the number of HSCs are increased associated with its biological properties of HSCs proliferation and counteration of apoptosis, when stimulated by fibrogenic stimuli [3][4][5]. However, limited understanding of the gene regulation made these characteristics of HSCs still vague and controversial until now.…”
Section: Introductionmentioning
confidence: 99%
“…However, the pharmacological research on SAA has lagged behind relative to SAB because of the difficulty in obtaining a large amount of pure compound due to the very low content in Danshen and the inability to synthesize SAA chemically. After the synthesis was resolved (Zhuang et al, 1996;Zhang et al, 2007), SAA attracted a great deal of attention for its beneficial effects as demonstrated by studies in animal and cell line models, such as protection against liver experimental injury and fibrosis (Hu et al, 2000;Liu et al, 2000aLiu et al, ,b, 2001Lin et al, 2006;Wu et al, 2007), protective effect against experimental impairment of memory (Du and Zhang, 1997) and protection against adriamycin toxicity of the rat heart (Lin et al, 1992). More recently, SAA was found to have some unique pharmacological actions from SAB, including reducing the blood level of glucose, glycosylated hemoglobin, and advanced glycation endproducts (AGEs), improving glucose metabolism disorders, and ameliorating oxidative stress of diabetic rats in our laboratory.…”
Section: Introductionmentioning
confidence: 99%